A Theological Review of the Concept of the Son of God Based on John 17:1–26 - Anen, Bruno Ikun; Lawalata, Mozes (International Journal of Christian Education and Philosophical Inquiry, 2025)
This study aims to examine the concept of the Son of God in the Gospel of John 17:1–26 from a theological perspective. The Gospel of John, one of the canonical Gospels, distinctively emphasizes the divine identity of Jesus as the Son of God. In chapter 17, Jesus prays to His Father in heaven, affirming His unique relationship as the Son of God. The research method employed is biblical text analysis using an exegetical approach. Data were collected from prominent theological sources and relevant academic literature. The findings indicate that the concept of the Son of God in John 17:1–26 encompasses several important theological dimensions, including: first, His equality with God the Father in divinity; second, the uniqueness of His relationship with the Father as the beloved Son; and third, His role in God's plan of salvation for humanity. The conclusion of this study is that the concept of the Son of God in John 17:1–26 affirms the divine identity of Jesus and reveals His intimate relationship with God the Father. This concept has significant theological implications for the Christian understanding of the divinity of Jesus Christ.